DYNAMIC CHARACTERISTICS ANALYSIS OF FLEXIBLE FOUNDATION VIBRATION ISOLATION SYSTEM - ZHANG DaoKun; HUO Rui; LI ShuYing; WANG ZhiDong (Jixie qiangdu)
A general coupled dynamic model of the isolation system is established,which is composed of isolation object,nonlinear isolators and flexible foundation. By transforming the system dynamic equation into an expression of initial value problem of differential equation,the calculation method of transmitted power flow is deduced,which is put forward to evaluation and analysis of isolation effectiveness. Based on an example of vibration isolation system of a small unmanned aircraft engine,the Runge-Kutta method is applied to simulation and estimation of power flow transmitted through nonlinear isolators with hypothetical different stiffness characteristics. It is presented that properly designed nonlinear isolators such as endowed with paralleled negative stiffness or piecewise linear stiffness could effectively reduce the power flow transmission of isolation system.